Long-term monitoring of precipitation chemistry in the U.S.: Insights into changes and condition. (15th January 2021) - Likens, Gene E.; Butler, Thomas J.; Claybrooke, Rodger; Vermeylen, Francoise; Larson, Robert
Abstract: Continuous monitoring of precipitation chemistry began at the Hubbard Brook Experimental Forest, NH in June 1963, and it was there that acid rain was discovered in North America. Some independent monitoring of precipitation chemistry in central New York was done in 1970–1971. The MAP3S network (Charlottesville, VA, Ithaca, NY, Penn State, PA, Whiteface Mt., NY) began in 1976 and became part of the National Atmospheric Deposition Program (NADP) in 1992. Using data from these long-term sites, and other published information, we show the status and temporal change of precipitation chemistry in the northeastern U.S. from 1963 to present. Combining records from all stations and networks gave better insights into the status and temporal trends of precipitation chemistry for the region particularly as detailed regional maps could be constructed from these data. Early maps of predicted pH (1955-56 and 1965-66) and individually measured pH values (1975-76), as well as cartoons provided important visual information about the occurrence and spread of acid rain in the northeastern U.S. These indicators of changing atmospheric chemistry were key in initiating federal policy necessary for improving air quality and for reducing atmospheric pollutant loading, which had led to acid rain in this area, starting in the 1950s. Analyzing combined records from Hubbard Brook and the 5 longest operating MAP3S/AIRMoN sites (IL11, NY67, DE02, PA15 and TN00) with a random coefficient model showed overall declines in annual concentrations of H +, SO4 2− and NO3 − from 1981 to 2017 of 85%, 80% and 66%, respectively. Calcium concentration declined by 14% and NH4 + showed no change during this period. Dry deposition of sulfur, NO3 − and Ca 2+ measured at co-located Clean Air Status and Trends Network (CASTNET) sites showed declines of 87%, 64% and <1%, respectively, during 2000–2017. As precipitation and air chemistry networks expanded to include the entire US (and Canada), dramatic improvements in precipitation chemistry nationwide, brought about by federal, clean air legislation, have been clearly documented. Highlights: Acid rain discovered in North America in 1963. Increasing precipitation acidity in eastern North America from the 1950's to the 1970's, and decreasing thereafter. National maps clearly convey occurrence and trends of acid rain to the public and policy makers. Declines of 85%, 80% and 66% in H +, SO4 2−, and NO3 − in precipitation chemistry from 1981 to 2017 in NE U.S. Comparable declines in sulfur and nitrate dry deposition.